2016
DOI: 10.1177/0031512515625388
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of The Cerebral Palsy Quality of Life Questionnaire in The Turkish Population

Abstract: This study examined the psychometric properties of the Turkish version of the Cerebral Palsy Quality of Life Questionnaire (CP QOL). A total of 149 primary caregivers completed the final version of the CP QOL-Primary Caregivers and the Children Health Questionnaire (CHQ) for children 4-12 years old (M age = 7.6 yr., SD = 2.5); 58 children with CP ages 9 to 12 years completed the CP QOL-Child and Health-Related Quality of Life Questionnaire for Children (Kid-KINDL) questionnaire. The Gross Motor Function Classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
(31 reference statements)
0
16
1
1
Order By: Relevance
“…The 16 included studies (Table ) reported on HRQoL of children and/or adolescents with CP and totaled 1579 participants (i.e. children and adolescents with CP; not inclusive of controls).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 16 included studies (Table ) reported on HRQoL of children and/or adolescents with CP and totaled 1579 participants (i.e. children and adolescents with CP; not inclusive of controls).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in eight countries: Turkey ( n =7), India ( n =2), Thailand ( n =2), Brazil ( n =1), China ( n =1), Indonesia ( n =1), Iran ( n =1), and Malaysia ( n =1) . Of the studies, there were two cross‐sectional, two case‐control, one prospective descriptive study, and four validation studies . The remaining studies did not specify, however they met criteria for cross‐sectional ( n =5) and case‐control ( n =2) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations